Discovery and characterization of cysteine-rich peptides in achyranthes bidentata roots (怀牛膝) - Kong, Teck Chuan (2019)
Cysteine-rich peptides (CRPs) have caught the interest of many researchers today with its naturally-formed, exceptionally stable disulfide bridges. Interestingly, recent research has increasingly relayed convincing evidence suggesting multiple uses of these CRP-containing derivatives as orally active drugs, usually in the context of administering herbal decoction in the practice of traditional Chinese medicine (TCM). This project focused on extracting the CRPs peptides from a widely known TCM herb, Achyranthes bidentata, to characterize its structure, determine the peptide sequence and verify its stability under different physiological conditions. Results indicated that a peptide, designated as an achyrantide (aB), was successfully isolated. The primary sequence of the peptide consists of 33 amino acids. Reduction and alkylation tests of aB1 conducted during disulfide determination verified that this peptide contains 6 cysteine residues, which forms 3 intramolecular disulfide bonds. The result confirmed that aB1 peptide is rich in cysteine residues, with a molecular weight of 3417.79 Da. In addition, stability tests were also carried out on aB1, demonstrating its high resistance against thermal degradation, reinforcing the hope of extracting CRPs from natural sources for medicinal uses.